MicroRNA-132-3p regulates cell proliferation, apoptosis, migration and invasion of liver cancer by targeting Sox4 - Huang, Jiansheng (Oncol Lett, 2020)
The present study investigated whether microRNA (miR)-132-3p targeted transcription factor SOX-4 (Sox4) for the inhibition of proliferation, migration, invasion and promotion of apoptosis in liver cancer (LC) cells. The expression of miR132-3p and Sox4 mRNA was evaluated by quantitative PCR and protein expression was determined by western blot analysis. Cell proliferation, apoptosis, migration, and invasion were assessed at different time points by the MTT assay, flow cytometry analysis, wound healing assay and Transwell migration assay, respectively. Bioinformatics prediction and luciferase assays were performed to validate and confirm Sox4as a potential target of miR-132p. There was a reduced expression of miR-132-3p in HepG2 and Huh7 cell lines compared with HccLM3 cells. Overexpression of miR-132-3p resulted in significant inhibition of proliferation and induction of apoptosis in LC cells. Moreover, migration and invasion of HepG2 cells were suppressed by over expressing miR-132-3p. However, downregulation of miR-132-3p in Hep-G2 cells promoted cell growth, invasion and migration and inhibited apoptosis. Bioinformatics analysis predicted Sox4 as a potential target of miR-132-3p, which was further confirmed by the luciferase reporter assay. In addition, an inverse association was observed between miR-132-3p and Sox4 expression. miR-132-3p may regulate the proliferation, apoptosis, migration and invasion of HepG2 cells by targeting Sox4.